Challenge or Consent? Understanding Losers' Reactions in Mass Elections. Issue 3 (4th February 2016) - Lago, Ignacio; Martinez i Coma, Ferran
Abstract : The conditions under which losers are willing to challenge the results of elections remain an open question. Using data from the Electoral Integrity Project for 66 democratic and non-democratic countries in 2012 and 2013, we measure how parties or candidates react once votes have been cast and one of them is declared the winner. Do they accept or challenge the results? This measure allows us to examine the causal mechanisms that account for the self-enforcing nature of democracies. Our findings show that losers' consent increases with free and fair elections and in more economically developed countries, while income inequality is not relevant. Additionally, the impact of free and fair elections is particularly important in more economically developed countries.